Timing of Postoperative Radiotherapy in Surgically Treated HPV-Positive Oropharyngeal Squamous Cell Carcinoma. (August 2019) - Townsend, Melanie; DeWees, Todd; Gross, Jennifer; Daly, Mackenzie; Gay, Hiram; Thorstad, Wade; Jackson, Ryan S.
Objective: Optimal timing of postoperative radiotherapy (PORT) remains understudied in human papillomavirus (HPV)–related oropharyngeal squamous cell carcinoma. Objectives are to determine if delays between surgery and radiotherapy, breaks during radiotherapy, disease, or patient factors are associated with recurrence or survival decrements in HPV-related disease. Design: Retrospective review. Setting: Academic medical center. Subjects: A total of 240 cases of HPV-positive oropharyngeal squamous cell carcinoma from 2000 to 2016. Methods: Patient and tumor characteristics (American Joint Committee on Cancer, eighth edition), delays to radiation initiation, and breaks during radiation were recorded. Overall survival (OS) and recurrence-free survival (RFS) were analyzed. Results: RFS and OS were not significantly affected by delays to PORT >6 weeks or by treatment intervals >100 days (surgery to PORT completion). Breaks during PORT significantly imparted an OS detriment (hazard ratio [HR], 2.4; 95% CI, 1.2-4.8). Advanced-stage disease was significantly associated with reduced RFS and OS. Subgroup analysis of stage I versus stage II/III disease found that >6 weeks to PORT initiation and treatment intervals >100 days did not significantly decrease RFS or OS in either stage group. Advanced-stage disease was significantly associated with worsened OS (HR, 6.6; 95% CI, 2.3-19.1) and RFS (HR, 5.3; 95% CI, 1.5-18.4). Breaks during PORT significantly reduced RFS (HR, 3.6; 95% CI, 1.2-10.8) and OS (HR, 3.2; 95% CI, 1.2-9.0) in the stage II/III subset. Conclusion: Delays to radiotherapy initiation and prolonged treatment time did not affect recurrence or survival in HPV-related oropharyngeal disease. Locoregionally advanced disease was consistently associated with worse outcomes. Breaks during PORT may affect recurrence and survival, although larger studies are needed to confirm this finding.